Educational Data Mining: A Survey of Analyzing Student Academic Performance Methods - Purani, K.D; Chaudhary, M.B (International Journal of Computer Sciences and Engineering, 2019)
Over the past decade, there has been a fast development in the advanced education system which prompts an enormous amount of data. Predicting students’ performance turns out to be all the more difficult because of this enormous measure of information in educational databases. However, this data from the educational department acts as a gold mine for institutions and also encourages the analysts and researchers to make a framework that can improve the general educating and learning process. Analysts and researchers apply Data mining techniques on educational data to explore it. Educational Data Mining helps in a big way to answer the issues of predictions and grouping of not only students but also the other stakeholders of education sectors. This paper talks about the utilization of different Data Mining techniques and tools that can be adequately utilized in noting the issues of predictions of students’ performance and their grouping.